The ocean quahog fishery of Maine - Maine. Dept. of Marine Resources. Extension Service. (Augusta : Maine Dept. of Marine Resources, 1977)
"A Maine Department of Marine Resources/Sea Grant/Publication" Cover title. Mode of access: Internet.